Proteomic study of the inhibitory effects of tannic acid on MRSA biofilm - Miao, Yang; Shuang, Wang; Qianwei, Qu; Xin, Liu; Wei, Peng; Hai, Yang; Yonghui, Zhou; Xinbo, Yu (Frontiers in Pharmacology, 2024)
The mechanism of tannic acid (TA) intervention in methicillin-resistant Staphylococcus aureus (MRSA, USA300) biofilm formation was explored using proteomics.The minimum inhibitory concentration (MIC) of TA against the MRSA standard strain USA300 was determined by two-fold serial dilutions of the microbroth. The effects of TA were studied using crystal violet staining. The morphology of TA-treated USA300 cells was observed using scanning electron microscopy and confocal laser scanning microscopy. Differentially expressed proteins (DEPs) were screened using proteomic and biological information analyses, and their transcriptional levels were verified using real-time quantitative PCR.The MIC of TA was 0.625 mg/mL, whereas 1/2 MIC (0.3125 mg/mL) of TA significantly inhibited biofilm formation without affecting bacterial growth (P < 0.01), and inhibited the formation of a complete three-dimensional biofilm structure. Using 1/2 MIC TA, 208 DEPs were identified, of which 127 were upregulated and 81 were downregulated. The transcript levels of genes (glnA, ribD, clpB, gap, and lukE) corresponding to randomly selected DEPs were consistent with the proteomics data (P < 0.05). Bioinformatic analysis showed that changes in MRSA strains after TA intervention primarily involved pyrimidine and purine metabolism, arginine biosynthesis, and the TCA cycle.Tannic acid produces an antibacterial effect on MRSA and can be used as a potential candidate for the development of anti-biofilm drugs, laying a foundation for the treatment of MRSA biofilm-induced infections.